The Political Policies Related to Islamic Education - Sutrisno, Sutrisno; Asha, Lukman; Fakhruddin, Fakhruddin (The Future of Education Journal, 2025)
This study employs the Systematic Literature Review (SLR) method to examine the influence of political policies on Islamic education in Indonesia. By collecting data from various journals, books, and relevant sources published in the last five years, the study finds that the relationship between political power and Islamic education is both strong and dynamic. Historically, Islamic education has often served as a tool for reinforcing authority, as well as a means of shaping national character. In the context of modern politics, especially during the reform era, Islamic education has been strengthened through policies such as educational decentralization, recognition of the status of madrasahs, integration of general and religious curricula, and financial support. However, challenges such as globalization, technological advancement, democratization, and moral decline remain serious threats that must be anticipated. Therefore, Islamic education must be adaptive and strategic to actively contribute to the development of a religious and morally grounded national civilization. This study emphasizes that Islamic education holds a strategic position within the national education system and must be continuously reinforced in response to global political and social dynamics.